2021
DOI: 10.1002/lpor.202100035
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Kerker Anapoles in Dielectric Microspheres

Abstract: High refractive index dielectric spheres present remarkable light-scattering properties in the spectral range dominated by dipolar modes. However, most of these properties are absent for larger spheres under plane wave illumination. Here, a proposal to unravel these dipolar regimes for larger particles under the illumination of a pure dipolar field is presented. This type of illumination ensures that the scattering response of the sphere is purely dipolar. In this scenario, it is shown that Kerker conditions a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(40 citation statements)
references
References 76 publications
1
39
0
Order By: Relevance
“…[39] and Ref. [25] that the conservation of helicity in scattering and the emergence of hybrid anapoles can only occur for lossless particles. Next, we show that conservation of helicity for the internal fields can only happen for the opposite case, i.e.…”
mentioning
confidence: 94%
See 3 more Smart Citations
“…[39] and Ref. [25] that the conservation of helicity in scattering and the emergence of hybrid anapoles can only occur for lossless particles. Next, we show that conservation of helicity for the internal fields can only happen for the opposite case, i.e.…”
mentioning
confidence: 94%
“…It is a widely used platform to discover new analytical effects, as well as to predict experimental measurements [20]. In particular, Mie Theory has been used to understand the role of helicity in a variety of scattering phenomena at the nanoscale, such as the so-called Kerker conditions [21,22], enhanced optical localization errors provided by optical mirages [23], or non-radiating sources [24] such as hybrid optical anapoles [25]. Moreover, helicity-dependent optical forces [26,27] have given rise to a large plethora of interesting phenomena with applications in the biomedical and pharmaceutical industries, ranging from chiral sensing [28][29][30] chiral sorting and enantioselective and enantiospecificdetection [31][32][33], to optical tweezers [34,35], among others.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…[14] Even though, the localized field is limited to the particle size of the order of d > λ, a number of interesting phenomena and applications have been observed in these low-index dielectric particles. For example, strong molecule-cavity coupling, [15] optical singularities that form two extreme hotspots near the particle poles, [16] higher order Fano resonances that provide giant magnetic field leading to super-oscillation effects, [17,18] the whispering gallery mode effect overcoming the diffraction limit leading to super-resolution imaging, [19] structured fields in the form of photonic hook and loops allowing new class of "on-chip" optical traps for anisotropic nanoobjects, [20] etc., indicate promising new directions of research enabled by low-index mesoscale dielectric particles.Recently, it was theoretically predicted, [21,22] one can unravel dipolar regimes in a homogenous lossless dielectric sphere with a wide range of size parameter and several refractive indices (n) under illumination with a pure dipolar field (PDF). More specifically, it was shown that the sectoral and propagating Nanophotonic phenomena, such as zero optical back scattering, nonradiating anapole states, etc.…”
mentioning
confidence: 99%